Thinking nature : an essay in negative ecology - McGrath, S. J., 1966- (New perspectives in ontology., 2019)
Tracks the history of the concept of nature from the Hebrew Bible, through Renaissance philosophy and science, to dark ecology. Critical of the post-humanist trend in contemporary eco-criticism, the author makes a compelling case for a new anthropocenic humanism - a humanism that is not at the expense of nature, and a naturalism that is not at the expense of the human. Nature as the stable backdrop of human civilization appears to have vanished. And yet the term "nature" remains vital to both metaphysics and to public ecological discourse. "Nature," in the author's view, is a living symbol, and can survive the extinction of one or another of its meanings. Whatever shape the new concept of nature will take, it must include the human being, the one who thinks nature